2014
DOI: 10.11646/phytotaxa.184.3.4
|View full text |Cite
|
Sign up to set email alerts
|

A new species of Orobanche (Orobanchaceae) from Turkey

Abstract: Orobanche turcica (Orobanchaceae) is described as a new species from Turkey. The new species is a close relative of O. anatolica. Morphological differences of the new taxon from closely related species are discussed. A distribution map, illustration, as well as pollen and seed microphotographs of the species are provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 5 publications
1
9
0
Order By: Relevance
“…Pujadas-Salvá and Velasco 2000;Joel and Eisenberg 2002;Hyun et al 2003;Mohamed and Musselman 2008). Furthermore, many researchers have reported that the two-lipped corolla with a long tube usually curved towards the lower lip is a characteristic trait of species from the section Orobanche (Restuccia et al 2009;Zare and Dönmez 2013), which was observed in O. picridis in the present study as well.…”
Section: Flower and Nectary Microstructuresupporting
confidence: 82%
See 2 more Smart Citations
“…Pujadas-Salvá and Velasco 2000;Joel and Eisenberg 2002;Hyun et al 2003;Mohamed and Musselman 2008). Furthermore, many researchers have reported that the two-lipped corolla with a long tube usually curved towards the lower lip is a characteristic trait of species from the section Orobanche (Restuccia et al 2009;Zare and Dönmez 2013), which was observed in O. picridis in the present study as well.…”
Section: Flower and Nectary Microstructuresupporting
confidence: 82%
“…The colour and microstructure of stigmata is highly important trait in the taxonomy of the genus Orobanche (Kreutz 1995). However, as shown by Zare and Dönmez (2013), the colour of the pistil in Orobanche may differ between species or within one species. The authors observed pink or yellow pistil stigmata in O. owerini and yellow, brown, red, or red-violet colour of this floral part in O. reticulata.…”
Section: Flower and Nectary Microstructurementioning
confidence: 99%
See 1 more Smart Citation
“…Species-differentiating characters used in this study to delimit distinction between species includes flower size, pattern of perigone lobes, pattern of diaphragm, pattern of window, size of aperture, number of processes, ramenta, and number of anthers. The application of flower differences have been widely used to differentiate between species in other groups of flowering plants for example in Magnoliaceae (Chen & Zeng, 2013), Hyacinthaceae (Uzunhisarcıklı et al, 2013), and Orobanchaceae (Zare & Dönmez, 2013 Diagnoses: This species is similar to Rafflesia azlanii by the perigone lobes covered by rows of coalesced white warts. It is different from Rafflesia azlanii by the absence of marginal ring of white warts on the periphery of the window, more rows of coalesced white warts on the perigone lobes, higher number of concentric rings of white warts on the window, larger number and rings of circular dots on the diaphragm, larger number and rings of processes on the upper surface of the disc, and more anthers (see Table).…”
Section: Methodsmentioning
confidence: 99%
“…24 species of Orobanche , 15 species of Phelipanche , two species of Diphelypaea , and one species of Cistanche Hoffmg. (Gilli , , Davis et al , Zare et al , Zare , Zare and Dönmez ). Based on phylogenetic reconstruvtion, Diphelypaea Nicolson and Orobanche anatolica Boiss.…”
mentioning
confidence: 99%